Probing the Combined Effect of Flunitrazepam and Lidocaine on the Stability and Organization of Bilayer Lipid Membranes. A Differential Scanning Calorimetry and Dynamic Light Scattering Study - Caruso, Benjamin (2012)
Combined effects of flunitrazepam (FNZ) and lidocaine (LDC) were studied on the thermotropic equilibrium of dipalmitoyl phosphatidylcholine (dpPC) bilayers. This adds a thermodynamic dimension to previously reported geometric analysis in the erythrocyte model. LDC decreased the enthalpy and temperature for dpPC pre- and main-transitions (ΔH p, ΔH m, T p, T m) and decreased the cooperativity of the main-transition (ΔT 1/2,m). FNZ decreased ΔH m and, at least up to 59 μM, also decreased ΔH p. In conjunction with LDC, FNZ induced a recovery of ∆T 1/2,m control values and increased ΔH m even above the control level. The deconvolution of the main-transition peak at high LDC concentrations revealed three components possibly represented by: a self-segregated fraction of pure dpPC, a dpPC–LDC mixture and a phase with a lipid structure of intermediate stability associated with LDC self-aggregation within the lipid phase. Some LDC effects on thermodynamic parameters were reverted at proper LDC/FNZ molar ratios, suggesting that FNZ restricts the maximal availability of the LDC partitioned into the lipid phase. Thus, beyond its complexity, the lipid–LDC mixture can be rationalized as an equilibrium of coexisting phases which gains homogeneity in the presence of FNZ. This work stresses the relevance of nonspecific drug–membrane binding on LDC–FNZ pharmacological interactions and would have pharmaceutical applications in liposomal multidrug-delivery.